PENGARUH FAKTOR PSIKOLOGIS, FAKTOR SOSIAL, FAKTOR FISIK DAN FAKTOR FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PELAYARAN GONOTIRTO PONTIANAK - B31108137, DHANI FITRIADY (Jurnal Manajemen Update, 2015)
THE INFLUENCE OF PSYCHOLOGICAL FACTORS, SOCIAL FACTORS, FINANCIAL FACTORS AND PHYSICAL FACTORS TOWARDS JOB SATISFACTION OF EMPLOYEES AT PT. PELAYARAN GONOTIRTO PONTIANAK Employees are assets that have influence and contribute the most in determining progress and success of an organization or company. The handling of human resources is not optimal and imprecise by management will hamper the attainment of the objectives of the organization or company. the sample of this research are all members of a population that numbered 65 people because in accordance with the selected sampling of retrieval techniques in the study, namely the Non Probability Sampling techniques. The data were analyzed by using statistical data processing package in the form of the Program SPSS 19.0 for windows. The results of the regression analysis indicates that physical factors have a positive relationship towards job satisfaction demonstrated by koefisein variables where a positive marked physical factor, while other factors do not have a positive relationship. Adjusted R Square value of R is a customized picture quality closer so that exploitation models in population. From the table it can be read that the Adjusted R Square is 8. Does that mean 8 independent variable (X) can be explained by the dependent variable i.e. job satisfaction of employees, while the remaining 92 are explained by other factors. Key words: factor of psychological, social, physical and financial, job satisfaction